Access to a telehealth falls prevention program: Mixed-method analysis from a health equity perspective - O’Neil, Jennifer; Dionne, Nathalie; Sauve-Schenk, Katrine; Savard, Jacinthe (Journal of Telemedicine and Telecare, 2026)
Introduction Access to falls prevention programs, addressing an important public health concern, is often limited for Francophone and Acadian minority communities. Technology has been used to deliver falls prevention programs, but health equity factors linked to improving its access for all are still poorly understood. This study aimed to document health equity factors influencing access from the perspective of older francophone adults in various communities across Canada. Methods Guided by the digital health equity framework, we used a sequential explanatory mixed method, including a descriptive sociodemographic questionnaire and semi-structured interviews, to document perspectives on access of persons who had completed different versions of a telehealth falls prevention program. Results Sixty-one participants from five provinces completed the sociodemographic questionnaire, of which most participants (n= 45) represented perspectives from francophone communities living in a minority situation. Results revealed that 91% of participants had access to a computer or tablet with adequate audio-visual components for telehealth. Twenty of these participants, from four provinces, shared their perspectives. The majority of them reported that falls prevention programs should be offered in their preferred language and with different delivery options that consider the social and safety preferences of participants. Eight recommendations informing policy and implementation emerged. Discussion Advocacy around digital connectivity is essential to ensure that all Canadians have equitable access to high-speed internet connections and proper infrastructure. Participants also raised the importance of adapting services to their linguistic realities, geographic location, safety, and basic needs to optimize the impact of the health services provided to them.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de synthèse - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Expériences de soins à domicile et enjeux linguistiques en Ontario : Perspectives d’aîné·es francophones, de proches aidant·es, d’intervenant·es et de gestionnaires. Rapport de recherche - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de recherche intégral présente des résultats détaillés, accompagnés de plusieurs citations de participants.

Home Care Experiences and Language Challenges in Ontario: Perspectives of Francophone Seniors, Family Caregivers, Frontline Care Providers, and Managers. Summary report - van Kemenade, Solange; Savard, Jacinthe; Benoît, Josée; Sauvé-Schenk, Katrine; Bouchard, Louise (Université d'Ottawa, 2026)
La présente étude visait à comprendre l’expérience des soins à domicile aux personnes aînées francophones en Ontario et l’impact des barrières linguistiques dans ce secteur, à partir des perspectives des gestionnaires, des intervenant·es, ainsi que des bénéficiaires et de leurs proches aidant·es. Elle cherchait également à explorer les variations dans l’offre de services en français en fonction du statut linguistique des fournisseurs de services. Ce rapport de synthèse décrit les principaux constats de l'étude, accompagnés de quelques citations de participants.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.